2000
DOI: 10.2355/isijinternational.40.244
|View full text |Cite
|
Sign up to set email alerts
|

Development of Waste Plastics Injection Process in Blast Furnace.

Abstract: At Keihin No. 1 Blast Furnace, waste plastics recycling system was installed in Oct. 1996. Before the installation of that system, the behavior of waste plastics injected into the blast furnace has been studied with the raceway hot model and the commercial blast furnace so as to investigate the possibility of effective waste plastics utilization in the blast furnace. From the observation of plastics particle injected into the raceway of blast furnace, it was estimated that combustibility of coarse plastics was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 6 publications
2
53
0
2
Order By: Relevance
“…The fundamental studies revealed it was feasible to inject coarse grains of waste plastics into blast furnace as an alternative to pulverized coal. 19,20) In 1999 injection quantity of waste plastics reached 45 000 tons in Japan, 21) and in 1996 the largest injection rate attained 60 kg/thm in Germany. 22) In this study, injection of hydrogen bearing matters, including humidified blasting (hereinafter abbreviated to HB), natural gas injection (NGI) and waste plastics injection (PLI) are investigated through numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental studies revealed it was feasible to inject coarse grains of waste plastics into blast furnace as an alternative to pulverized coal. 19,20) In 1999 injection quantity of waste plastics reached 45 000 tons in Japan, 21) and in 1996 the largest injection rate attained 60 kg/thm in Germany. 22) In this study, injection of hydrogen bearing matters, including humidified blasting (hereinafter abbreviated to HB), natural gas injection (NGI) and waste plastics injection (PLI) are investigated through numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…One was ''light'' waste plastic having the apparent density of 0.52-0.56 g/cm 3, and the other was ''heavy'' plastic having the apparent density of 0.86 g/cm 3 . In the case of the light waste plastic, as shown in Fig.…”
Section: Influence Of Plastic Addition On Coke Qualitymentioning
confidence: 99%
“…where W is the mass of added plastic (g), N is the number of the added plastic particles, q is the plastic density (g/cm 3 ), r is the mean radius of the plastic (cm) and SA (cm 2 /g) is the specific surface area of the added plastic particles. As shown here, the total surface area is inversely proportional to the plastic radius and density.…”
Section: Influence Of Plastic Addition On Coke Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of waste plastics in the blast furnace has been reported in several papers. [4][5][6] However, the massive combustion technology of waste plastics under the low oxygen excess rate is required for lowering reducing agent rate remarkably. Some studies on low temperature reduction of wustite or lowering carburization temperature of metal have been reported.…”
Section: Introductionmentioning
confidence: 99%